Analysis of Suitability of Mangrove Ecosystem as Beach Tourism in the Mangrove Ecotourism Category in Tongke-Tongke Village, Sinjai Regency - Auliah, Armi; Yulianda, Fredinan; Boer, Mennofatria (Agrikan Jurnal Agribisnis Perikanan, 2024)
Ecotourism activities can be said to be a concept of utilizing natural resources with a conservation approach for tourism development. In managing mangrove ecotourism in Tongke-tongue Village, the government and area managers should assess the suitability of the area for mangrove ecotourism so that it can become an evaluation material to be better able to improve empowerment and management of the mangrove ecosystem in Tongke-tongue Village so that the area is better maintained. This research aims to analyze the suitability of the mangrove ecosystem as a mangrove ecotourism area in Tongke-tongue Village, Sinjai Regency. This research was carried out in August-September 2023 in the Mangrove Ecosystems Area of Tongke-tongue Village. The analysis used is the Tourism Suitability Index (IKW). The results of the study of the data obtained explain that area I has a value of 2.25 in the S category (suitable), area II has a value of 2.50 in the SS category (very appropriate), area III has a value of 2.50 in the SS category (very suitable ), and area IV gets a score of 2.35 with category S (appropriate). The entire observation area shows the level of suitability of the area to be used as mangrove ecotourism.